Sistem Informasi Perpustakaan pada SMP N 1 Karang Bahagia Berbasis Web dengan Metode Waterfall - Anggita Julaeha; Nurhadi Surojudin; E Edora (LPPM STIKOM Tunas Bangsa, 2023)
SMPN 1 Karang Bahagia is a junior high school (SMP) which is located on Jl. Raya Pulo Bambu, Karangbahagia, Kec. KarangHappy, Bekasi Regency, West Java 17530. Of course the school has a library, but the data processing and information information system for the library that is running is still done manually, namely using a control card that is only stored in books without duplicating data, so that when the user wants to borrow or returning them must write the book title, author, and date on the control card so that transactions using a manual system tend to take longer and are prone to errors in data writing so that it is possible to cause efficiency problems over time or long processes in data management and information. Besides that, the method for developing this system is to use the waterfall method, where the steps of this method begin with an analysis of system requirements, and continue with the collection of materials, design, manufacture, testing (redesign if not appropriate) and system application. The results of this research are in the form of a Library Information System website for SMPN 1 Karang Bahagia, which will be able to facilitate librarians in the process of borrowing books because they have gone through the system in the process. The development of this Library Information System is made in a web-based application that uses Apache with mod_ssl as the web server, PHP as the web programming language, and MySQL as the software that handles the database.